Considering one's option when the fish leave: a case study of the traditional commercial handline fishery of the Southern Cape - Gammage, Louise Carin (Marine Research (MA-RE) Institute, 2015)
Today, many pressures (socio-economic, resource scarcity, policy, and regulation) make fishers and their communities vulnerable on a variety of fronts. These pressures threaten fishing communities along the South African coast. Both natural and social changes in the traditional handline fishery affect the social-ecological system of a region as a whole. Fishers need to cope with these local global changes and require systems that support their strategies to achieve resilience. Furthermore, stressors that drive variability in the fishery system occur on multiple temporal and spatial scales thereby exposing fishers and communities to multiple stressors. The impact and interplay of these stressors at multiple scales need to be taken into account to develop a clear understanding of social-ecological linkages if sustainable livelihoods are to be promoted and guaranteed. There is however a shortage of appropriately scaled, context-specific data that is needed to inform various decision-making processes. To this end, participant-led research was conducted in six communities in the Southern Cape, where 50 participants were interviewed over a period of 6 months in 2013/2014. The interviews were an attempt to gather and record perceptions and knowledge regarding stressors that are responsible for the social- ecological system and ultimately affect the fishers' ability to fish successfully. Based on this knowledge, the research was aimed at gaining insight into what strategies are currently employed to ensure sustainable livelihoods. The data presented does not only offer valuable insights into the day-to-day experiences of the group of fishers, but also expose various knowledge gaps that exist in micro-scale interactions that influence the fishery system. This is achieved by first providing an analysis of various stressors, which include the impacts and responses to climate variability, challenges presented by policy and regulatory frameworks, social and economic considerations, challenges presented by infrastructure and political considerations. The adaptation, coping, and reaction strategies implemented are analysed using a place-based context and variability of strategies employed between each specific place is discussed. Apart from highlighting knowledge gaps, the development of a more complete understanding of current reacting, coping and adaptive strategies as well as the drivers behind the decisions contained in this thesis, provides valuable insight into a fishery system that is not well-described which underscores the need for context-specific research at smaller scales.